Regulation of Discrete Functional Responses by Syk and Src Family Tyrosine Kinases in Human Neutrophils - Thornin Ear; Olga Tatsiy; Frédérick L. Allard; Patrick P. McDonald (Journal of Immunology Research)
Neutrophils play a critical role in innate immunity and also influence adaptive immune responses. This occurs in good part through their production of inflammatory and immunomodulatory cytokines, in conjunction with their prolonged survival at inflamed foci. While a picture of the signaling machinery underlying these neutrophil responses is now emerging, much remains to be uncovered. In this study, we report that neutrophils constitutively express various Src family isoforms (STKs), as well as Syk, and that inhibition of these protein tyrosine kinases selectively hinders inflammatory cytokine generation by acting posttranscriptionally. Accordingly, STK or Syk inhibition decreases the phosphorylation of signaling intermediates (e.g., eIF-4E, S6K, and MNK1) involved in translational control. By contrast, delayed apoptosis appears to be independent of either STKs or Syk. Our data therefore significantly extend our understanding of which neutrophil responses are governed by STKs and Syk and pinpoint some signaling intermediates that are likely involved. In view of the foremost role of neutrophils in several chronic inflammatory conditions, our findings identify potential molecular targets that could be exploited for future therapeutic intervention.